2015
DOI: 10.5049/ebp.2015.13.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Loop Diuretics in Clinical Practice

Abstract: Diuretics are commonly used to control edema across various clinical fields. Diuretics inhibit sodium reabsorption in specific renal tubules, resulting in increased urinary sodium and water excretion. Loop diuretics are the most potent diuretics. In this article, we review five important aspects of loop diuretics, in particular furosemide, which must be considered when prescribing this medicine: (1) oral versus intravenous treatment, (2) dosage, (3) continuous versus bolus infusion, (4) application in chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 26 publications
3
87
0
2
Order By: Relevance
“…Furosemide inhibits the sodium-potassiumchloride (Na + -K + -2Cl -) co-transporter located in the apical membrane of tubular cells in the thick ascending limb in the kidney. 1,3 Furosemide binds to plasmatic proteins and is not filtrated by the glomeruli in a large proportion. Therefore, as many other diuretics, it needs to be secreted by proximal tubular cells in order to reach its site of action.…”
Section: Results: Furosemide Pretreatment Increased Both the Expressimentioning
confidence: 99%
“…Furosemide inhibits the sodium-potassiumchloride (Na + -K + -2Cl -) co-transporter located in the apical membrane of tubular cells in the thick ascending limb in the kidney. 1,3 Furosemide binds to plasmatic proteins and is not filtrated by the glomeruli in a large proportion. Therefore, as many other diuretics, it needs to be secreted by proximal tubular cells in order to reach its site of action.…”
Section: Results: Furosemide Pretreatment Increased Both the Expressimentioning
confidence: 99%
“…In a secondary analysis excluding Shah et al's study, we found that continuous infusion was associated with significantly higher total urine output in 24 h in comparison with bolus administration (p < 0.01). This may be explained by the fact that peak effects of bolus administration are achieved in the first 1–2 h by rapidly increasing sodium excretion, which then declines progressively over time . A consistent plasma drug concentration of furosemide from continuous infusion may have a more consistent diuretic effect, producing greater weight reduction and total urine output in 24 h than following bolus administration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CRI potentially reduces the so-called diuretic resistance like the rebound phenomenon and maintains more consistent diuresis (Adin et al 2003). In addition, CRI has been associated with lower peak plasma concentrations of furosemide, which may be associated with a lower incidence of side effects (Michael Felker 2010;Oh and Han 2015).…”
Section: Discussionmentioning
confidence: 99%